Życie codzienne nauczycieli szkół powszechnych w Okręgu Mazurskim w świetle wspomnień i pamiętników (część I) - Radziszewska, Maria (Biuletyn Historii Wychowania, 2011)
The article concerns the problem of public school teachers’ daily lives in the region of Masuria. The analysis has included such components of everyday life as: travel to Warmia and Masuria, the reasons for choosing the profession, education, work areas, work conditions and methods as well as the forms of alimentation in the school. The issue of teachers’ daily lives deserves special attention because of a specific situation of Polish education in Warmia and Masuria in the school years 1944/1945–1945/1946. Teachers were mainly engaged in organizing the basic conditions for functioning of Polish schools in order to promote the Polish language among the youth and children of different nationalities and cultures. Their daily lives were influenced by determining the final border of the District of Masuria, the action of managing this land and the constant risk and problems with the staff, rooms and money. The article does not only discuss teachers’ daily professional lives (Part I) but also their personal lives (Part II). There is certainly a need for broader studies by using a variety of source materials. In order to present the issue, the author has used mainly sources of an autobiographical nature – memories and diaries.